About fuzzy fixed point theorem in the generalized fuzzy fractal space. - M. G. AL-Saidi, Nadia; Md. Said, Mohamad Rushdan; M. Ahmed, Adil (Pushpa Publishing House, 2011)
The Banach fixed point theorem has applications in several branches of science. Many authors prove this theorem in different types of fuzzy metric spaces and fuzzy fractal spaces. The aim of this paper is to prove the Banach fixed point theorem in a new generalized space called multi fuzzy fractal space.